Can the “multi-plan integration” pilot policy facilitate the low-carbon transformation of land use? Evidence from empirical studies in China - Qian, Jingjing; Zhang, Xiaomin; Xu, Ning (Frontiers in Environmental Science, 2025)
The “multi-plan integration” pilot policy (MIPP) is a crucial measure for establishing a territorial spatial planning system and promoting the sustainable use of land. This study treats the implementation of MIPP as a quasi-natural experiment, using panel data from 283 Chinese cities between 2006 and 2019 to examine the impact of MIPP on the low-carbon transformation of land use (LCTLU). The results indicate that MIPP significantly promotes LCTLU, a conclusion supported by a series of robustness analyses. In cities where MIPP was implemented, the level of land low-carbon use increased by an average of 2.87%. MIPP primarily advances LCTLU by reducing land resource misallocation and leveraging economies of scale. Compared with southern regions, large cities, and non-resource-based cities, MIPP is more effective in promoting LCTLU in northern regions, small- to medium-sized cities, and resource-based cities. Moreover, MIPP more effectively promotes LCTLU in non-smart and non-innovative cities than in smart and innovative cities.